(untitled) (CIPEEX, 2025)
Mastopexy with implants is a frequently performed surgical technique in women seeking to improve the shape and firmness of their breasts. This procedure combines breast lift with the placement of implants, aiming not only for an aesthetic result but also for the overall satisfaction of patients with their appearance. Postoperative satisfaction is a critical indicator of surgical success, directly influencing patients’ quality of life. OBJECTIVE: The present study aims to analyze the satisfaction rate of patients after undergoing mastopexy with implants, using data from recent studies to understand the factors that contribute to patient satisfaction or dissatisfaction. METHOD: An integrative literature review was conducted using articles obtained from databases such as PubMed, Scielo, and Google Scholar. The descriptors used were ’mastopexy’, ’breast implants’, and ’patient satisfaction’, covering studies published between 2022 and 2023. RESULTS: The reviewed studies indicate that most patients undergoing mastopexy with implants report a high level of satisfaction with the aesthetic results. In one study, 98% of patients stated that the results met or exceeded their expectations, and 85% considered breast size ’ideal’. However, the rate of complications, such as capsular contracture and surgical revisions, remains a significant concern, although these factors did not substantially reduce overall satisfaction. Revision rates range between 13% and 48% within the first 3 to 5 years after surgery. Additionally, satisfaction with breast shape was also high, with notable differences between those who opted for isolated implants versus those who underwent a combination with mastopexy. CONCLUSION: It is concluded that mastopexy with implants presents a high satisfaction rate among patients, despite possible complications and surgical revisions. The combination of mastopexy with implants not only improves the aesthetic appearance of the breasts but also contributes to increased self-esteem and quality of life for patients. However, it is essential that patients are well informed about the potential risks and the need for revisions so they can make an informed decision.